Approaches to Model of Psychological Support of Athletes at All Stages of Sports Carrer (The Journal of Psychology and Sociology, 2015)
The general theoretical approaches to the construction of model of psychological support for athletes at all stages of sports career are stated. The psychological work with regard to age factor and personality development as a subject of activity is proposed. Orientation, criteria and methods of psychological work with athletes are marked. The ways of implementation into psychological work of coach with regard to difficulties of every stage of sports career are revealed.Hypothesis of research is as follows: theoretical foundation of the model of psychological support for athletes and realization of the model in practice may help on the decrease of negative consequences of «early sportive professionalization» and promote the increase of performance of athletes within all their career in sports.
Keywords: model; psychological support; sports career.